Plan de negocios para la creación de una cancha de fútbol de césped sintético ubicado en el barrio Brazales de la ciudad de Latacunga durante el año 2015 - Chango Lagla, Digna Patricia (2016)
The idea of a business plan for the creation of a soccer court with synthetic grass located in Brazales neighborhood Latacunga city during 2015, was aiming to provide services that are aligned with people´s expectations who want to have a fun time, and the lack of appropriate places since it is one of the main obstacles has reduced the sports practice in the neighborhood largely thus adopting makeshift soccer courts on streets and sidewalks, obstucting often vehicular traffic and endangering the players and spectators safety by a market study applying research methodologies such descriptive, documentary and research tools such as observation and survey obtaining projections of supply and demand, unsatisfied demand, prices were also analyzed taking the projected annual inflation reference….